Pathology, bacteriology and molecular studies on caseous lymphadenitis in Camelus dromedarius in the Emirate of Abu Dhabi, UAE, 2015-2020. - Abdelnasir Mohammed Adam Terab; Ghada El Derdiri Abdel Wahab; Hassan Zackaria Ali Ishag; Nasereldien Altaib Hussein Khalil; El Tigani Ahmed El Tigani-Asil; Farouk Mohamed Hashem; Abdelmalik Ibrahim Khalafalla; Asma Abdi Mohamed Shah; Salama Suhail Mohammed Al Muhairi (PLoS ONE)
Caseous lymphadenitis (CLA) or pseudotuberculosis is a chronic zoonotic bacterial disease caused by Corynebacterium pseudotuberculosis, which affects livestock and humans. This study aimed to describe the pathology, bacteriology and confirm the identity of the pathogen by 16S rRNA gene sequencing in Camelus dromedarius. A total of 12 camels with suspected CLA in three regions of Abu Dhabi Emirate (Abu Dhabi, Al Ain and Al Dhafra), United Arab Emirate (UAE) were subjected to clinical and postmortem examinations from January 2015 to December 2020. Clinically, camels were emaciated and showed the presence of external caseous abscesses suggestive of CLA. Postmortem examination showed multiple abscesses of variable sizes with caseous material encapsulated by fibrous tissue in the liver, lungs, muscle, and lymph nodes. Following clinical and postmortem examination, blood, pus and different tissue samples were collected for subsequent analysis. Histopathological examination of all organs stained with Hematoxylin and Eosin (H&E) indicated a central caseo-necrotic core that was admixed with bacterial colonies and infiltration of chronic inflammatory cells, surrounded by a pyogenic membrane, and an outer fibrous connective tissue capsule. Bacterial culture identified the isolates of Corynebacterium pseudotuberculosis biotype ovis strain, and these isolates were shown to be sensitive to all antibiotics tested (penicillin, ampicillin, Co-trimoxazole, enrofloxacin and tetracycline). Moreover, the identity of the isolates was confirmed by partial sequencing of the 16S rRNA gene which showed a 100% identity to Corynebacterium pseudotuberculosis. Phylogenetic analysis based on 16S rRNA gene sequence clearly differentiates Corynebacterium pseudotuberculosis from other species of Corynebacterium. Briefly, this study provided the basic information for infection of Corynebacterium pseudotuberculosis in Camels and will help in controlling of this pathogen in the region.